CORPORATE AGGRESSION: A COMPREHENSIVE REVIEW OF PRICE WAR - Alzoubi, Ahlam (European Journal of Business and Strategic Management, 2020)
Purpose: Despite the significance that prices take in companies, it appears that this factor has not researched extensively by academics and marketers. Therefore, this article investigates price war to provide a comprehensive reference about it. Methodology: The researcher has conducted an extensive study of the available relevant literature about the price wars. Marketing research and empirical studies from marketing, industrial organizations and economics has provided the framework for this research. Findings: It is essential to employ appropriate analytic tools for strategic planning of price war. Smart management, along with technical skills, experience and leadership work together for organizational success. Contribution: This study is significant for compiling a wide range of analytical tests and suggesting their appropriate use on right time. This study is helpful for the companies as it has not only provided step by step strategic planning for price wars but has explained when and how to start price wars.